EVALUASI PENGENDALIAN INTERNAL SISTEM PENJUALAN TUNAI MENGGUNAKAN METODE CONTROL MATRIX - Siti Eryana Sugiharto Putri; SUJI ABDULLAH SALEH (Indonesian Accounting Literacy Journal, 2022)
Cash sales are one of the important activities in a company to ensure the continuity of the company's business. For this reason, an internal control system is needed that can make cash sales activities more effective and efficient. The purpose of this study is to determine the implementation and evaluation of the cash sales internal control system at the Sana Farma 2 Pharmacy. The method used is a qualitative method. The technique used in data collection is interviews, observation, and documentation which is strengthened by a questionnaire. The data analysis tool used is the control matrix based on the COSO (Committee of Sponsoring Organizations) framework. The results of the research show that the implementation of the cash sales internal control system at the Sana Farma 2 Pharmacy has fulfilled several internal control objectives, although it is not optimal because there are still several elements that have not been implemented. We recommend that Apotek Sana Farma 2 correct the shortcomings of the internal control system for more effective inventory management. Keywords: Internal control system, cash sales, control matrix, COSO.